2020
DOI: 10.1111/jcmm.15974
|View full text |Cite
|
Sign up to set email alerts
|

The stiffness‐controlled release of interleukin‐6 by cardiac fibroblasts is dependent on integrin α2β1

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…Elevated IL-6 levels in the culture medium are required for increased cell stiffness in Piezo1-transfected HAF, and for induction of PiCS in neighboring, non-Piezo1-transfected cells, i.e., IL-6 acts in an autocrine and in a paracrine manner. There is some evidence in the literature pointing to a connection between IL-6 and integrin signaling in cardiac fibroblasts, for example in response to differences in matrix stiffness [ 63 ]. It remains to be evaluated whether IL-6 signaling itself is sufficient, and integrin signaling is required for paracrine induction of PiCS.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated IL-6 levels in the culture medium are required for increased cell stiffness in Piezo1-transfected HAF, and for induction of PiCS in neighboring, non-Piezo1-transfected cells, i.e., IL-6 acts in an autocrine and in a paracrine manner. There is some evidence in the literature pointing to a connection between IL-6 and integrin signaling in cardiac fibroblasts, for example in response to differences in matrix stiffness [ 63 ]. It remains to be evaluated whether IL-6 signaling itself is sufficient, and integrin signaling is required for paracrine induction of PiCS.…”
Section: Discussionmentioning
confidence: 99%
“…Homeostasis of the extracellular matrix within the heart is dependent on cardiac fibroblasts, which account for 60-70% of cells in the human heart. These cells are responsible for the synthesis and breakdown of the extracellular matrix within the heart (1,2). They are also able to detect physical and biological stimuli; these stimuli may change the activity of the cardiac fibroblasts and their potential for collagen synthesis (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…These cells are responsible for the synthesis and breakdown of the extracellular matrix within the heart (1,2). They are also able to detect physical and biological stimuli; these stimuli may change the activity of the cardiac fibroblasts and their potential for collagen synthesis (2,3). It has been found that heart fibroblasts secrete cytokines with autocrine or paracrine regulatory effects (2,3): Fibroblasts isolated from the heart of a patient with heart failure were found to release higher levels of cytokines under inflammatory conditions, and this effect was independent of hypoxia (3).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations